2018
DOI: 10.3988/jcn.2018.14.4.555
|View full text |Cite
|
Sign up to set email alerts
|

Interarm Blood Pressure Difference is Associated with Early Neurological Deterioration, Poor Short-Term Functional Outcome, and Mortality in Noncardioembolic Stroke Patients

Abstract: Background and PurposeInterarm differences in the systolic and diastolic blood pressures (IASBD and IADBD, respectively) are found in various populations, including stroke patients, but their significance for stroke outcomes has rarely been reported. We aimed to determine the associations of IASBD and IADBD with early neurological deterioration (END), functional outcome, and mortality.MethodsThis study included 1,008 consecutive noncardioembolic cerebral infarction patients who were admitted within 24 hours of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Therefore, it is of great importance to identify factors associated with END in patients with acute minor stroke or TIA due to steno‐occlusive arterial disease. Based on the previous studies, several clinical and biological factors, such as older age, the initial neurological severity, diabetes mellitus, and blood pressure, might influent the development of END in patients with general ischemic stroke . To our best known, few studies focus on patients with acute minor stroke or TIA due to steno‐occlusive arterial disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is of great importance to identify factors associated with END in patients with acute minor stroke or TIA due to steno‐occlusive arterial disease. Based on the previous studies, several clinical and biological factors, such as older age, the initial neurological severity, diabetes mellitus, and blood pressure, might influent the development of END in patients with general ischemic stroke . To our best known, few studies focus on patients with acute minor stroke or TIA due to steno‐occlusive arterial disease.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous studies, several clinical and biological factors, such as older age, the initial neurological severity, diabetes mellitus, and blood pressure, might influent the development of END in patients with general ischemic stroke. [8][9][10][11] To our best known, few studies focus on patients with acute minor stroke or TIA due to steno-occlusive arterial disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al found that IAD ≥10 mm Hg was associated with the presence and increased burden of cerebral small‐vessel diseases in noncardioembolic stroke patients. Another study suggested that an IAD of ≥10 mm Hg could be a useful indicator for the risks of early neurological deterioration, poor functional outcome, and mortality . Recently, increasing attention has been paid to better understanding the clinical outcome of sIAD, the most reported include subclinical atherosclerosis, left ventricular hypertrophy, aortic aneurysms, aortic dissection, and cardiovascular disease .…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that an IAD of ≥10 mm Hg could be a useful indicator for the risks of early neurological deterioration, poor functional outcome, and mortality. 24 Recently, increasing attention has been paid to better understanding the clinical outcome of sIAD, the most reported include subclinical atherosclerosis, 25 left ventricular hypertrophy, 5 aortic aneurysms, 15 aortic dissection, and cardiovascular disease. 10 Inconsistent with above studies, three studies 4,5,26 compared cerebrovascular (stroke, cerebral atherosclerosis, and transient ischemic attack) outcomes among groups defined by sIAD of 10 mm Hg or more, and one study 26 compared outcomes at cutoff of 15 mm Hg or more, cumulative estimates were not statistically significant at either cutoff.…”
Section: Discussionmentioning
confidence: 99%